Experience with cladribine tablets for highly active multiple sclerosis in everyday clinical practice - S. V. Petrov; O. V. Boyko; A. N. Boyko (Неврология, нейропсихиатрия, психосоматика, 2020)
Cladribine tablets are a new drug for the immune reconstitution therapy of highly active multiple sclerosis (HAMS). After discussing the characteristics of action of the drug in clinical trials, the authors give their own experience of its use in the Moscow Multiple Sclerosis Center.Objective: to assess their own experience with cladribine tablets in the treatment of HAMS patients in everyday clinical practice.Patients and methods: In 2018–2020, a total of 14 patients with HAMS and an average exacerbation frequency of 2.42 per year (34 exacerbations) received a full cycle of cladribine therapy. The patients independently purchased the drug for individual indications. Prior to starting therapy and every subsequent 6 months, all the patients underwent contrast-enhanced magnetic resonance imaging (MRI) of the brain, cervical and thoracic spine, and chest X-ray, Expanded Disability Status Scale (EDSS) scoring, clinical blood analysis, lymphocyte subpopulation estimation, biochemical blood analysis. The levels of leukocytes, lymphocytes, and lymphocyte subpopulations were estimated after one- and two-year cladribine tablet therapy cycles.Results and discussion. During a two-year cladribine tablet therapy cycle, there were only 2 exacerbations (0.1 per year); the EDSS values stabilized, while they slightly decreased; according to MRI, the number of foci declined substantially from 78 (an average of 3.12 per image) before treatment to 6 (an average of 0.2 per image) after 2 years of treatment. No serious adverse events were recorded in patients taking cladribine tablets. By the end of the first year of treatment, the level of lymphocytes returned to normal in all the patients. The similar picture was noted after the second cycle of therapy. More than two-thirds of patients showed a decline in CD19+ B lymphocytes. An anti-B-cell effect was recorded even in patients who had normal absolute lymphocyte counts, as shown by clinical blood analysis. The findings demonstrated the efficacy and safety of cladribine tablets in patients with HAMS.Conclusion. Cladribine tablets are a highly effective treatment for HAMS.